ANALISIS TERMOGRAVIMETRI Spirulina platensis DENGAN KATALIS Ni/Al-SBA-15 RASIO Si/Al=10 MENGGUNAKAN LAJU PEMANASAN 10°C/MENIT - Anisa, Nia Nur; Subagyono, R.R. Dirgarini Julia Nurlianti; Allo, Veliyana Londong (PROSIDING SEMINAR KIMIA, 2024)
The thermogravimetric analysis of Spirulina platensis with Ni/Al-SBA-15 catalyst (Si/Al ratio = 10) using a heating rate of 10°C/min has been conducted. This study was performed to determine and analyze the chemical decomposition process of Spirulina platensis with a pyrolysis heating rate of 10°C/min. Based on the characterization results, Spirulina platensis has a moisture content of 8.34% and an ash content of 7.18%. The TG and DTG curves show the active pyrolysis temperature range of Spirulina platensis microalgae with Ni/Al-SBA-15 catalyst between approximately 155-496°C. The chemical decomposition of Spirulina platensis with Ni/Al-SBA-15 catalyst occurs in three stages: 1. water evaporation, 2. active pyrolysis, where the decomposition of carbohydrate, protein, and lipid compounds takes place, and 3. passive pyrolysis caused by gasification and the formation of non-volatile carbon compounds that vaporize to form CO and CO2 gases at high temperatures. Keywords: Thermogravimetry, Spirulina platensis, Pyrolysis, Ni/Al-SBA-15